QUALITY EVALUATION OF THE TPP POWER GENERATING UNITS WEAR RECONDITIONING - E. M. Farhadzadeh; A. Z. Muradaliyev; Yu. Z. Farzaliyev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Reconditioning of the power generating unit worn equipment and devices is conducted during the scheduled repair period. Quality of wear reconditioning is evaluated by technical state and repair work implementation. Quality of the repair work execution characterizes logistical activities of the power station and the repair services and is rated by a five-grade scale. There are three technical conditions: adequate, subject to reservations, falling short of the technical standard documentation requirements. In practical work these constraints give place to essential ambiguity of the decision. Further to regulating techniques by way of informational support, the authors propose conducting the wear-reconditioning quality evaluation (repair quality) accordingly the technical-and-economic indexes pattern of change. The paper recommends applying similarly the fivegrade system in evaluating the power generating unit technical state and distinguishes intolerable, dissatisfactory, fair, good and model estimates. The study demonstrates the assessment criteria dependence on the character of reliability and economical efficiency of performance variation after the repair with increase or decrease of the technical-and-economic indexes in reference to their mean, minimum and maximum values before the repair. The cases ascribed to intolerable quality of the wear reconditioning are those with one or more technical-and-economic indexes that not only failed to improve their values but deteriorated, and at that they became the worst amongst observable values. The model quality estimate of the wear reconditioning is allotted under condition that the power unit technical-and-economic index valuations after the repair not merely improved but also exceeded the best among those under observation. The developed method and algorithm for quality evaluation of the scheduled repair implementation contribute to practical realization of the independent monitoring. This monitoring not merely accounts for the information on alteration in the power generating unit emergency-switching standing time number and duration but also for the data of measurement and computation of technical-and-economic indexes. The technical-and-economic indexes variation analysis refinement allows significant rise in the repair work quality evaluation immediacy and in doing so reduces the costs associated with indistinct performance reliability and economical efficiency ranging of the power units based upon specified requirements.